Alveolar rhabdomyosarcoma with regional nodal involvement: Results of a combined analysis from two cooperative groups. Issue 3 (27th November 2020) - Gallego, Soledad; Chi, Yueh‐Yun; De Salvo, Gian Luca; Li, Minjie; Merks, Johannes H.M.; Rodeberg, David A.; van Scheltinga, Sheila Terwisscha; Mascarenhas, Leo; Orbach, Daniel; Jenney, Meriel; Million, Lynn; Minard‐Colin, Veronique; et al.
Abstract: Background: Treatment of children and adolescents with alveolar rhabdomyosarcoma (ARMS) and regional nodal involvement (N1) have been approached differently by North American and European cooperative groups. In order to define a better therapeutic strategy, we analyzed two studies conducted between 2005 and 2016 by the European paediatric Soft tissue sarcoma Study Group (EpSSG) and Children's Oncology Group (COG). Methods: We retrospectively identified patients with ARMS N1 enrolled in either EpSSG RMS2005 or in COG ARST0531. Chemotherapy in RMS2005 comprised ifosfamide + vincristine + dactinomycin + doxorubicin (IVADo), IVA and maintenance (vinorelbine, cyclophosphamide); in ARST0531, it consisted of either vincristine + dactinomycin + cyclophosphamide (VAC) or VAC alternating with vincristine + irinotecan (VI). Local treatment was similar in both protocols. Results: The analysis of the clinical characteristics of 239 patients showed some differences between study groups: in RMS2005, advanced Intergroup Rhabdomyosarcoma Study Group (IRS) and large tumors predominated. There were no differences in outcomes between the two groups: 5‐year event‐free survival (EFS), 49% (95% confidence interval [CI]: 39‐59) and 44% (95% CI: 30‐58), and overall survival (OS), 51% (95% CI: 41‐61) and 53.6% (95% CI: 40‐68) in RMS2005 and ARST0531, respectively. In RMS2005, EFS of patients with FOXO1 ‐positive tumors was significantly inferior to those with FOXO1 ‐negative (49.3% vs 73%, P = .034). In contrast, in ARST0531, EFS of patients with FOXO1 ‐positive tumors was 45% compared with 43.8% for those with FOXO1 ‐negative. Conclusions: The outcome of patients with ARMS N1 was similar in both protocols. However, patients with FOXO1 fusion‐negative tumors enrolled in RMS2005 showed a significantly better outcome, suggesting that different strategies of chemotherapy may have an impact in the outcome of this subgroup of patients.